Efektivitas Akun Podcast Mendoan Sebagai Media Hiburan Dikalangan Remaja Surabaya - Krisna Bagus Prayoga; Jokhanan Kristiyono (DIGICOM : Jurnal Komunikasi dan Media, 2022)
The phenomenon that the researcher points out is the proliferation of Laskar Mendoan (fans of the Mendoan podcast) which has made the podcast able to push the podcasts of top artists. All of the podcast episodes are mostly in Javanese, which not everyone understands. The purpose of this study is to determine the effectiveness of the Mendoan podcast in providing entertainment content through podcasts. In a study, it is necessary to have a method or method for researchers as a step to solve a problem to achieve a goal. The type of research used is descriptive quantitative. According to Sugiyono, the research method is a scientific method used to obtain accurate data with the aim of discovering, developing, and proving certain knowledge so that in part it can be used to understand and solve problems (Sugiyono, 2012). Based on the results of the t-test, podcast mendoan obtained a partial effect on listener interest. Based on the results of the F test, the podcast variable Mendoan simultaneously affects listeners' interest. It is hoped that podcasters can continue to maintain the quality of their content and develop the themes they present so that in the future it can be more developed and accepted by various levels of society.